“Brain MR spectroscopy in autism spectrum disorder—the GABA excitatory/inhibitory imbalance theory revisited” - Brix, Maiken K.; Ersland, Lars; Hugdahl, Kenneth; Grüner, Renate; Posserud, Maj-Britt; Hammar, Åsa; Craven, Alexander R.; Noeske, Ralph; Evans, C. John; Walker, Hanne B.; Midtvedt, Tore; Beyer, Mona K. (Frontiers in Human Neuroscience, 2015)
Magnetic resonance spectroscopy (MRS) from voxels placed in the left anterior cingulate cortex was measured from 14 boys with Autism Spectrum Disorder (ASD) and 24 gender and age-matched typically developing (TD) control group. Our main aims were to compare the concentration of γ-aminobutyric acid (GABA) between the two groups, and to investigate the relationship between brain metabolites and autism symptom severity in the ASD group. We did find a significant negative correlation in the ASD group between Autism Spectrum Screening Questionnaire (ASSQ) and GABA+/Cr, which may imply that severity of symptoms in ASD is associated with differences in the level of GABA in the brain, supporting the excitatory/inhibitory (E/I) imbalance theory. However we did not find a significant difference between the two groups in GABA levels.